3D Macroporous Nitrogen‐Enriched Graphitic Carbon Scaffold for Efficient Bioelectricity Generation in Microbial Fuel Cells. Issue 4 (3rd November 2016) - You, Shijie; Ma, Ming; Wang, Wei; Qi, Dianpeng; Chen, Xiaodong; Qu, Jiuhui; Ren, Nanqi
Abstract : Microbial fuel cell (MFC) can generate electricity based on oxidation of organic compounds by exoelectogens, giving rise to a promising potential for recovering electrical energy from organic wastewater. The structure and property of anode materials have inherent impact to extracellular electron transfer (EET), an interfacial process that greatly limits bioelectricity production of MFC. Herein, a three dimensional (3D) macroporous nitrogen‐enriched graphitic carbon (NGC) scaffold is fabricated from commercially available melamine foam using facile pyrolysis method. The NGC electrode is demonstrated to promote EET efﬁciently, achieving a power density of 750 mW m −2 based on pure cultured Shewanella oneidensis MR‐1 in acetate‐feeding MFC. The unique 3D open‐cell structure not only offers habitats for colonization of electroactive bioﬁlm up to a maximal density but also provides macroporous architecture for internal mass transfer without concern of bio‐blocking and bio‐fouling. Additionally, nitrogen incorporation also plays a signiﬁcant role in enhancing EET, where pyrrolic nitrogen is much more active than graphitic and pyridinic nitrogen as indicated by density functional theory calculation. This work provides a proof‐of‐concept demonstration of a high‐efﬁciency, cost‐effective, easily scaling‐up, and environmentally friendly anode material of bioelectrochemical systems for electricity generation, hydrogen production, and pollutant degradation. Abstract : A 3D macroporous nitrogen‐enriched graphitic carbon scaffold is fabricated with melamine foam serving as precursor by facile pyrolysis process. The unique macroporous structure, high nitrogen content, and good conductivity are favorable for extracellular electron transfer between electrode and exoelectrogens, making it a promising anode material of bioelectrochemical systems for electricity generation, hydrogen production, and pollutant degradation.